Interpreting myocardial perfusion scintigraphy using single-photon emission computed tomography. Part 1 - Czaja, Monika; Wygoda, Zbigniew; Duszańska, Agata; Szczerba, Dominik; Głowacki, Jan; Gąsior, Mariusz; Wasilewski, Jarosław P. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
This article discusses the protocol for myocardial perfusion scintigraphy performed with single-photon emission computed tomography (SPECT). Indications for SPECT are listed with consideration given to the results of the increasingly more common angio-CT examinations of the coronary arteries (multislice computed tomography). The paper also presents basic information about interpreting the results, including the scores of left ventricle myocardial perfusion using the 17-segment polar map, and explains the concept of total perfusion deficit.